Improved image quality at 256-slice coronary CT angiography in patients with a high heart rate and coronary artery disease: comparison with 64-slice CT imaging. (November 2015) - Oda, Seitaro; Katahira, Kazuhiro; Utsunomiya, Daisuke; Takaoka, Hiroko; Honda, Keiichi; Noda, Katsuo; Oshima, Shuichi; Yuki, Hideaki; Namimoto, Tomohiro; Yamashita, Yasuyuki
Background: The 256-slice computed tomography (CT) scanners with wider detector coverage and faster gantry rotation speed are now available. The performance of scanners that feature a rotation speed of 270 ms at coronary CT angiography (CCTA) has not been evaluated in patients with a higher heart rate. Purpose: To evaluate the image quality of 256-slice CT with faster gantry rotation speed in patients undergoing CCTA. Material and Methods: We enrolled 886 patients; 357(40.3%) underwent study on a 64-slice CT at a rotation speed of 420 ms, the other 529 (59.7%) were examined using a 256-slice CT scanner at 270 ms. Two observers judged the image quality of 2658 imaged coronary arteries on a 4-point scale. Results: The mean image quality score was significantly higher for the 256 - than the 64-slice CT scans (3.94 ± 0.28 vs. 3.73 ± 0.61; P  < 0.01). There was no significant difference in the image quality scores between 64 - and 256-slice scans in patients whose heart rate (HR) was <60 bpm. However, in patients whose HR exceeded 60 bpm these scores were significantly higher for 256-slice CT images ( P  < 0.01). Conclusion: CCTA performed on the 256-slice CT scanner yielded significantly better image quality in patients with an HR exceeding 60 bpm.